EFFECTS OF PULMONARY REHABILITATION ON SYSTEMIC INFLAMMATION IN INDIVIDUALS WITH SEVERE ASTHMA (CIPEEX, 2025)
Introduction: Severe asthma is characterized by persistent inflammation, airway remodeling, and lung function limitation, with symptoms persisting despite pharmacological treatment. Pulmonary rehabilitation (PR), especially aerobic exercise, not only improves functional capacity and reduces dyspnea but also modulates systemic inflammation, including cytokines and other proteins, making it a promising complementary approach. Objectives: To evaluate the effects of PR on systemic levels of cytokines and anti-fibrotic proteins in individuals with severe asthma. Methods: The study included 21 patients with severe asthma, diagnosed according to GINA criteria and evaluated by a pulmonologist. Inclusion criteria considered the absence of comorbidities, ongoing pharmacological treatment for ≥6 months, and age between 20–60 years. Venous blood was collected for hematological analysis and quantification of pro-inflammatory mediators (IL-1beta, IL-5, IL-6, IL-13), anti-inflammatory mediators (IL-1ra, IL-10), pro-fibrotic proteins (VEGF, TSLP), and anti-fibrotic proteins (relaxin-3, klotho) using ELISA. Data were analyzed using GraphPad Prism 5.0, with normality assessed by the Kolmogorov-Smirnov test and paired and independent Student’s t-tests, considering p